The history and character of the Islamic built environment - Omer, Spahic (Arah Pendidikan Sdn Bhd., 2009)
This book discusses several vital, yet often misunderstood, themes pertaining to the history and character of the Islamic built environment. The themes discussed are: - An introduction to the character of early Islamic architecture (from 11H/632CE to 97H/715CE) - A reading of the philosophy of rich decoration in Islamic architecture - City planning in Ibn Khaldun's thought - Housing planning policies of the Prophet Muhammad (pbuh) - The significance of the Rock (Sakhrah) inside the al-Aqsa Mosque - Socio-political conditions surrounding the creation of the Dome of the Rock - The Holy Qur'an on the built environment.